1997
DOI: 10.1049/el:19971291
|View full text |Cite
|
Sign up to set email alerts
|

1 m long continuously-written fibre Bragg gratings for combined second- and third-order dispersion compensation

Abstract: The authors present the realisation of high-quality 1 m long continuouslywritten fibre Bragg gratings designed to compensate both 2nd and 3rd order fibre dispersion. These compact devices are ideal for counteracting the effects of fibre dispersion in high bit-rate transmission systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 2 publications
0
26
0
1
Order By: Relevance
“…Note that previous work has indicated that dispersion-slope correction can in certain instances also be an issue for such broadband spread-spectrum transmission schemes since it can serve to skew the chip alignment in the decoded signal [21]. No such effects were apparent in our current experiments; however, it should be appreciated that thirdorder dispersion compensation can also be incorporated into the design of dispersion compensating Bragg gratings if required [22], [23]. As mentioned previously, the dispersion compensating grating used in our experiments was also fabricated using the same technique and with the same phase mask used to fabricate the coding/decoding SSFBGs.…”
Section: System Characterizationmentioning
confidence: 59%
“…Note that previous work has indicated that dispersion-slope correction can in certain instances also be an issue for such broadband spread-spectrum transmission schemes since it can serve to skew the chip alignment in the decoded signal [21]. No such effects were apparent in our current experiments; however, it should be appreciated that thirdorder dispersion compensation can also be incorporated into the design of dispersion compensating Bragg gratings if required [22], [23]. As mentioned previously, the dispersion compensating grating used in our experiments was also fabricated using the same technique and with the same phase mask used to fabricate the coding/decoding SSFBGs.…”
Section: System Characterizationmentioning
confidence: 59%
“…Subsequently, fiber Bragg gratings became one of the most important passive fiber optic components, used for dispersion compensation [9][10][11][12], fiber laser pump reflectors [13][14][15] and in various sensing applications. Sensing fields such as strain [16], pressure [17][18][19], ultrasonic waves [20][21][22], force [23][24][25], acceleration [26,27], magnetic field [28,29], and temperature [30][31][32] were covered by FBGs over the years.…”
Section: Waveguide and Fiber Bragg Gratingsmentioning
confidence: 99%
“…Compensation schemes for multiple orders of dispersion are well known and include the use of phase modulators [8], tunable fiber Bragg gratings [10][11][12], and concatenation of spans of specialty fibers [13,14]. However, fluctuations of the impairments, mainly due to temperature drifts and stress variations, also occur in long-distance fiber transmission, requiring adaptative solutions able to tune the compensation in real time [15][16][17].…”
Section: Introductionmentioning
confidence: 99%